2017
DOI: 10.4103/aer.aer_98_17
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose succinylcholine to facilitate laryngeal mask airway insertion: A comparison of two doses

Abstract: Background and Aims:Around the world, the use of the laryngeal mask airway (LMA) is becoming more common for different surgeries accounting for it being the dominant choice of airway in numerous surgeries. Although propofol is known to blunt the laryngeal reflexes often patient movement, coughing, and gagging occur on insertion. This study aims to identify the optimum dose of succinylcholine required to facilitate LMA insertion comparing placebo, 0.1 mg/kg and 0.25 mg/kg of succinylcholine. Further objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…The results are comparable with the findings of Leah George et al where he divided 283 patients into three groups to receive either normal saline, 0.1mg/kg succinylcholine or 0.25mg/kg succinylcholine and found that 84.9% patients had excellent overall insertion conditions in the 0.25 mg/kg group. 1 The results are also in correlation with the study conducted by Korula S et al, where he used low dose succinylcholine (0.35mg/kg) for insertion of LMA during thiopental induction in comparison with atracurium (0.08mg/kg). He found the inserting conditions and ease of insertion to be better in the succinylcholine group.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results are comparable with the findings of Leah George et al where he divided 283 patients into three groups to receive either normal saline, 0.1mg/kg succinylcholine or 0.25mg/kg succinylcholine and found that 84.9% patients had excellent overall insertion conditions in the 0.25 mg/kg group. 1 The results are also in correlation with the study conducted by Korula S et al, where he used low dose succinylcholine (0.35mg/kg) for insertion of LMA during thiopental induction in comparison with atracurium (0.08mg/kg). He found the inserting conditions and ease of insertion to be better in the succinylcholine group.…”
Section: Discussionsupporting
confidence: 85%
“…12 Two different doses of succinylcholine 0.1mg/kg and 0.25mg/kg were compared by Leah George et al for LMA insertion and observed that overall insertion conditions were better in 0.25mg/kg group than 0.1mg/kg group. 1 After much deliberation, the dose of 0.25mg/kg of succinylcholine was chosen for the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated ED50 for the total patient group was 35.11 μg·kg − 1 [24]. The effective dose in our study differed from the 48 μg·kg − 1 that was estimated as the ED95 of cis-atracurium by Belmont et al [25] and differed from the ED50 and ED95 of 30 μg·kg − 1 and 53 μg·kg − 1 , respectively, reported by Lepage et al [26]. In our study, the SBP was significantly lower in the 20 μg·kg − 1 group at T2 (i.e., anaesthesia induction timepoint), T3, and T4, and was indistinguishable from the SBP in the 30 μg·kg − 1 group and the 50 μg·kg − 1 group.…”
Section: Discussioncontrasting
confidence: 78%